"There's Plenty More Clunge in the Sea": Boyhood Masculinities and Sexual Talk. (April 2018) - Clark, Jessica
This article sets out to analyze the dominant sexual discourses embedded and negotiated within the television sitcom The Inbetweeners . Sex is a highly visible element of the program, marking it as a prevailing feature of the life of the teenage boy, paradoxically natural yet problematic. The performances draw upon and reproduce governing discourses of sexuality and gender. Of the potential themes, three are considered here. First, sex is represented as ubiquitous within the boys' narratives, an assumed attribute of (the transition to) the performance of successful adult masculinity. Second, individual (hetero) sexuality is policed through peer-led homophobic banter and humor. Third, girls are objectified by boys, demonstrating the role of gendered relations in the governance of femininity and the discursive sanctions, which define masculinity through objects of desire. This article reveals some of the sexual subjecthoods made available to young men through televised representation, and considers their position within the wider sexual landscapes of boyhood.